Ethnobotanical research of tree species used in wood carving in Southern Benin: Perspective for sustainable forest conservation - Dossou-Yovo, Hubert Olivier; Kindomihou, Valentin; Sinsin, Brice (Ethnobotany Research and Applications, 2020)
Background: This research aimed at assessing the diversity of timber species used in wood carving in southern Benin, identify various sources of wood as well as most species used. We also stated that wood is recorded as the most used part for carving. The scarcity or availability of species with quality wood and their causes in recent years were assessed. Carvers’ willingness to contribute to species conservation was also documented. With a perspective of sustainable forest conservation, the impact of wood carving activity on forests was also assessed. Methods: A preliminary survey was conducted to determine the number of wood carvers in three districts of Southern Benin. A semi-structured questionnaire was used to collect data from twelve wood carvers. Data was analyzed through descriptive statistics, mainly using percentages and mean. We determined the Use Value of the most used species for woods in order to assess their relative importance. Results: Twenty-two species were used in wood carving with most species having red or yellow wood. The purchase of wood in industrial markets was the predominant source, followed by the direct purchase from plantation and tree owners. Among the main woody species used including Diospyros mespiliformis, Chlorophora excelsa, Tectona grandis and Gmelina arborea, the Use Value (i.e. relative importance in terms of diversity of uses) was the highest with G. arborea and C. excelsa. While most of carvers mainly accused logging of making wood scarce and destroying forests and plantations, only a minority (25%) own G. arborea and A. auriculiformis plantations. Carvers indicated their willingness to have plantations of T. grandis and G. arborea for personal use and trade. Promoting reforestation and timber species plantation are plausible through imntegrated policies, such as: (i). Developing appropriate silviculture; (ii). Sensitizing actors about forest conservation, the need for appropriate silviculture by giving priority to the quality of products and techniques at all stages; (iii). Strengthening forestry services capacities, consolidating technical achievements and monitoring forestry actions; (iv). Establishing, consolidating and developing sustainable self-promotion capacities of rural populations mainly women's groups, based on the integrated land development, beneficiaries' entrepreneurial participation and the commercialization chain promotion at community and regional scales (v). Creating and supporting institutional structures in monitoring learning; (vi). Promoting the advent of self-managed rural forestry based on the principle that reforestation really develops whether it can generate its own resources. Conclusions: A diverse range of tree species are used in carving in Southern Benin. The most used species were D. mespiliformis, C. excelsa, T. grandis and G. arborea. Gmelina arborea and C. excelsa had the highest Use Value. Carvers indicated their willingness to contribute to species plantation and conservation. Wood carving had an impact on forest and thus a need to promote reforestation and plantation, and to raise awareness with wood carvers on sustainable resource utilization and management. Key words: Fragmentation; Plantations;Reforestation; Use Value; Wood Carving